IMPACT OF METABOLIC CONTROL IN PREULCERATIVE PHASE OF DIABETIC FOOT - Irfan Ahmeti; Milco Bogoev; Gordana Pemovska; Tatjana Milenkovic; Branka Krstevska; Arben Taravari (SHMSHM / AAMD, 2011)
Aim. To estimate impact of metabolic disturbances in type 2 diabetic patients (T2DM) and risk for ulceration in preulcerative phase of diabetic foot syndrome (DFS). Material and methods. In this prospective study following parameters are estimated: duration, smoking, BMI, BP, HbA1c, TG, HDL, LDL, fundoscopy and measurements for risk score of DFS. Groups were stratified according measurements : 0–low risk, 1–medium risk, 2-high risk, and 3–very high risk. Results. From 100 patients, 53% were female and 47% male. Mean duration of T2DM 10, 47 ±4, 77 year. Smokers are registered to have 43%, Results of measurements for risk score stratifications have been in V1: score 0-29 %, 1–3%, 2-18% and 3–18% and in V2 in score 0-17 %, 1–39%, 2-19% and 3–25%. BMI was recorded as follows: normal (18-25 kg/m2) 14%, overweighed (25-30 kg/m2) 71% and obese (>30 kg/m2) 15%. Mean HbA1c in V1 was recorded: 0-7,6%, 1-7,9%, 2-8,5% and 3-8,2% (p<0,005), and in V2: score 0-7.26%, 1-7.46%, 2-7, 54% and 3-7, 54%. Systolic BP divided regarding scores is measured: score 0–136 mmHg, 1–142 mmHg, 2–145 mmHg, 3–142 mmHg. Mean levels of TG were: 0-1,97 mmol/L, 1-2,37 mmol/L, 2-2,3 mmol/L, 3-2,6 mmol/L. Mean levels of HDL: 0–1,06 mmol/L, 1–1,02 mmol/L, 2–0.97 mmol/L, 3–1,00 mmol/L. Mean levels of LDL: 0–3,69 mmol/L, 1–4,27 mmol/L, 2–4,05 mmol/L 3–4,09 mmol/L. Conclusion: Bad management of T2DM have impact in early appearance of DFS and early progression from low to high score for foot ulceration.
Keywords: diabetic foot; metabolic control; preulcerative phase